2017
DOI: 10.18203/2349-3933.ijam20173236
|View full text |Cite
|
Sign up to set email alerts
|

A study of various factors associated with sexual dysfunction in males with type 2 diabetes mellitus

Abstract: Background: SD is very common in type 2 diabetic men. Many middle aged and older adults with diabetes are sexually active, but the rate of sexual inactivity is higher than in non-diabetic subjects. The objective of this study was to study various factors associated with sexual dysfunction in males with type- 2 diabetes mellitus.Methods: A total of 60 male type 2 diabetic subjects were studied. They were divided in to two groups, 42 subjects with SD were in one group and 18 subjects with normal sexual function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…A consistent risk factor for ED includes increasing age, in both the diabetic and general population. 12 In the present study, a significant association was observed between age and prevalence of ED; the proportion of ED in diabetic patients increased with age, and the highest J o u r n a l P r e -p r o o f prevalence was observed in the >60-year age category (48.1%) and the lowest in the ≤30-year age category (0.00%). In another Indian study, the prevalence of ED was found to be 10.3% and 54.6% in <40-year and 40-59-year age-groups of patients, respectively.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 55%
See 3 more Smart Citations
“…A consistent risk factor for ED includes increasing age, in both the diabetic and general population. 12 In the present study, a significant association was observed between age and prevalence of ED; the proportion of ED in diabetic patients increased with age, and the highest J o u r n a l P r e -p r o o f prevalence was observed in the >60-year age category (48.1%) and the lowest in the ≤30-year age category (0.00%). In another Indian study, the prevalence of ED was found to be 10.3% and 54.6% in <40-year and 40-59-year age-groups of patients, respectively.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 55%
“…Similar to the results of our study, Jakka and Ramesh had reported orgasmic dysfunction in about 38% of their study population, comprising males with T2DM. 12 Further, the study by Malavige et al reported premature ejaculation in 40% of patients with diabetes. They also reported a strong association between ED and premature ejaculation (odds ratio = 4.41; 95% confidence interval = 2.08-9.39) in patients with T2DM.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
See 2 more Smart Citations